Targeted sequencing may facilitate differential diagnostics of pulmonary tumours: a case series - Kajsa Ericson-Lindquist; Anna Johansson; Per Levéen; Göran Elmberger; Göran Jönsson; Johan Staaf; Hans Brunnström (BMC, 2017)
Abstract Background Histopathological diagnosis is important for prognostication and choice of treatment in patients with cancer in the lung. Metastases to the lungs are common and need to be distinguished from primary lung cancer. Furthermore, cases with synchronous or metachronous primary lung cancers (although infrequent) are often handled differently than cases with lung cancer with intrapulmonary metastasis or relapse, respectively. In some cases, morphology and immunohistochemical staining is not sufficient for certain diagnosis. Methods The present study included six cases where molecular genetic analysis in form of pyrosequencing or targeted next-generation sequencing was of value for certain diagnosis of selected tumours in the lung. Results Two of the included cases were rare metastases to the lung; colorectal cancer with IHC profile consistent with primary lung cancer and malignant adenomyoepithelioma of the breast, respectively, where molecular genetic analysis was of aid for proving the relationship to the primary tumour. The other four cases were multiple lung adenocarcinomas where molecular genetic analysis was of aid to distinguish between intrapulmonary metastasis and synchronous tumour. Conclusions Comparison of molecular genetic profile may be an important tool for determination of relationship between tumours in some situations and should always be considered in unclear cases. Further studies on concordance and discordance of molecular genetic profiles between spatially or temporally different tumours with common origin may be helpful for improved diagnostics of pulmonary tumours.